Sorafenib and Piperine co-loaded PLGA nanoparticles: Development, characterization, and anti-cancer activity against hepatocellular carcinoma cell line - Sulaiman S. Alhudaithi; Mohd Abul Kalam; Lama Binobaid; Raisuddin Ali; Mohammed M. Almutairi; Wajhul Qamar; Hessa Bin Hithlayn; Atheer Almutairi; Abdullah K. Alshememry (Elsevier, 2024)
Hepatocellular carcinoma (HCC) exhibits high mortality rates in the advanced stage (>90 %). Sorafenib (SORA) is a targeted therapy approved for the treatment of advanced HCC; however, the reported response rate to such a therapeutic is suboptimal (<3%). Piperine (PIP) is an alkaloid demonstrated to exert a direct tumoricidal activity in HCC and improve the pharmacokinetic profiles of anticancer drugs including SORA. In this study, we developed a strategy to improve efficacy outcomes in HCC using PIP as an add-on treatment to support the first-line therapy SORA using biodegradable Poly (D, L-Lactide-co-glycolide, PLGA) nanoparticles (NPs). SORA and PIP (both exhibit low aqueous solubility) were co-loaded into PLGA NPs (PNPs) and stabilized with various concentrations of polyvinyl alcohol (PVA). The SORA and PIP-loaded PNPs (SP-PNPs) were characterized using Fourier Transform Infrared (FTIR) Spectroscopy, X-ray Powder Diffraction (XRD), Dynamic Light Scattering (DLS), and Scanning Electron Microscopy (SEM), Release of these drugs from SP-PNPs was investigated in vitro at both physiological and acidic pH, and kinetic models were employed to assess the mechanism of drug release. The in vitro efficacy of SP-PNPs against HCC cells (HepG2) was also evaluated. FTIR and XRD analyses revealed that the drugs encapsulated in PNPs were in an amorphous state, with no observed chemical interactions among the drugs or excipients. Assessment of drug release in vitro at pH 5 and 7.4 showed that SORA and PIP loaded in PNPs with 0.5 % PVA were released in a sustained manner, unlike pure drugs, which exhibited relatively fast release. SP-PNPs with 0.5 % PVA were spherical, had an average size of 224 nm, and had a high encapsulation efficiency (SORA ∼ 82 %, PIP ∼ 79 %), as well as superior cytotoxicity compared to SORA monotherapy in vitro. These results suggest that combining PIP with SORA using PNPs may be an effective strategy for the treatment of HCC and may set the stage for a comprehensive in vivo study to evaluate the efficacy and safety of this novel formulation using a murine HCC model.